Smoothing, discounting, and demand for intra-household control for recipients of conditional cash transfers - Diego Aycinena; Szabolcs Blazsek; Lucas Rentschler; Betzy Sandoval (Journal of Applied Economics, 2019)
Inter-temporal preferences are important determinants of investment decisions, including investments in human capital. Yet, little is known about these preferences for recipients of conditional cash transfers (CCTs). We simultaneously estimate utility curvature (preference for consumption smoothing), discounting, and present biasedness for such recipients. We also introduce a financially motivated method of measuring willingness to forgo funds to control household finances. We find that female participants in a CCT program in Guatemala have very high degrees of utility curvature and low discount factors, which may lead to low levels of investment by participants in the human capital of the household. We also find that intra-household conflict is not significantly related to consumption smoothing, discounting, or present bias.
Keywords: 330; consumption smoothing; discounting; field experiments; intra-household control